The Influence of Audit Fee, Independence, and Competency On Audit Quality - KUSMAYASARI, Dewi; BILGIES, Ana Fitriyatul; DAMAYANTI, Damayanti; SUHARSONO, Judi (Journal of Governance, Taxation and Auditing, 2023)
This study examines the influence of audit fees, independence, and competence on audit quality in KAP Surabaya and Malang. Data was collected using a saturated sampling approach, wherein questionnaires were distributed to gather responses. The response rate for the study was 78%, with a total of 39 completed questionnaires out of the 50 distributed. The collected data was analyzed using multiple linear regression in SPSS Version 25. The findings indicate significant results. Firstly, higher audit fees positively impacted audit quality, suggesting that auditors receiving higher fees devote more time and resources to conducting thorough audits, leading to better quality outcomes. Secondly, independence had a positive and significant effect on audit quality, implying that auditors maintaining a higher level of independence demonstrate professional skepticism, objectivity, and impartiality, resulting in higher-quality audits. Thirdly, competence positively influences audit quality, indicating that auditors with more excellent technical knowledge, experience, and professional skills perform more accurate and reliable audits, thereby enhancing audit quality. These findings emphasize the importance of adequate audit fees, promoting independence, and enhancing auditor competence to ensure high-quality audits. Audit firms and regulators should consider these factors when formulating audit policies and procedures. This study provides valuable insights into the relationship between audit fees, independence, competence, and quality. By understanding these factors, stakeholders can strive to improve audit practices and standards, ultimately leading to more effective and reliable auditing processes.